2014
DOI: 10.1016/j.eplepsyres.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain volumes and cognition in childhood epilepsy: Does size really matter?

Abstract: Purpose Recent studies have correlated neurocognitive function and regional brain volumes in children with epilepsy. We tested whether brain volume differences between children with and without epilepsy explained differences in neurocognitive function. Methods The study sample included 108 individuals with uncomplicated nonsyndromic epilepsy (NSE) and 36 healthy age- and gender-matched controls. Participants received a standardized cognitive battery. Whole brain T1-weighted MRI was obtained and volumes analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…The changes in EEG-recorded waves will depend on the number of epileptic seizures. Referring to findings of the study which are also confirmed by other research (Zelko, Pardoe, Blackstone, Jackson & Berg, 2014) we can acknowledge the superiority of biological factors over other psycho-social factors in determining the severity of symptoms of the occurrence of epilepsy in children.…”
Section: Discussionsupporting
confidence: 86%
“…The changes in EEG-recorded waves will depend on the number of epileptic seizures. Referring to findings of the study which are also confirmed by other research (Zelko, Pardoe, Blackstone, Jackson & Berg, 2014) we can acknowledge the superiority of biological factors over other psycho-social factors in determining the severity of symptoms of the occurrence of epilepsy in children.…”
Section: Discussionsupporting
confidence: 86%
“…[148]20134healthy72.600.00reportedperformanceWAIS-III: ss3270.34Zelko et al . [149]20134healthy14.9053.00reportedFSIQWAIS or WISC: voc, sim, pc, bd, arith, ds, ss360.25Zelko et al . [149]20134patients14.6049.00reportedFSIQWAIS or WISC: voc, sim, pc, bd, arith, ds, ss1080.23Zelko et al .…”
Section: Methodsmentioning
confidence: 99%
“…[149]20134healthy14.9053.00reportedFSIQWAIS or WISC: voc, sim, pc, bd, arith, ds, ss360.25Zelko et al . [149]20134patients14.6049.00reportedFSIQWAIS or WISC: voc, sim, pc, bd, arith, ds, ss1080.23Zelko et al . [149]20134patients14.6049.00reportedverbalWAIS or WISC: voc, sim1080.23Zelko et al .…”
Section: Methodsmentioning
confidence: 99%
“…Recent neuroimaging research using magnetic resonance imaging (MRI) has sought to shed light on possible shared neural mechanisms underlying epilepsy and ADHD comorbidity 1 , 10 , 37 – 39 . While some evidence implicates shared neurobiological abnormalities 40 , 41 , other studies suggest that independent factors are at play 10 , 40 .…”
Section: Discussionmentioning
confidence: 99%